2019
DOI: 10.1112/jlms.12226
|View full text |Cite
|
Sign up to set email alerts
|

Ulam floating bodies

Abstract: We study a new construction of bodies from a given convex body in Rn which are isomorphic to (weighted) floating bodies. We establish several properties of this new construction, including its relation to p‐affine surface areas. We show that these bodies are related to Ulam' s long‐standing floating body problem which asks whether Euclidean balls are the only bodies that can float, without turning, in any orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…The expressions in the above theorem can thus be used to define the affine surface area for all convex bodies. Around the same time, different extensions of the affine surface area to arbitrary convex bodies were given by Leichtweiß [92] and Lutwak [105] and afterwards several more have been found, e.g., [81,124,178]. It has been shown that all those extensions coincide.…”
Section: Affine Surface Area An Important Affine Invariant From Affimentioning
confidence: 98%
“…The expressions in the above theorem can thus be used to define the affine surface area for all convex bodies. Around the same time, different extensions of the affine surface area to arbitrary convex bodies were given by Leichtweiß [92] and Lutwak [105] and afterwards several more have been found, e.g., [81,124,178]. It has been shown that all those extensions coincide.…”
Section: Affine Surface Area An Important Affine Invariant From Affimentioning
confidence: 98%
“…Geometric descriptions in the sense of (2.6) and (2.7) of L p -affine surface area also exist. We refer to e.g., [28,50,51,56,58].…”
Section: Background and Definitionsmentioning
confidence: 99%
“…In special cases, our construction yields L p -centroid bodies (see [37] and [47,Sec. 10.8]) and Ulam floating bodies recently introduced in [27]. The latter form a particularly important special setting, which is confirmed by showing that all transformations K → E e (K) can be expressed in terms of Ulam floating bodies.…”
Section: Introductionmentioning
confidence: 73%
“…The following result establishes relationships between average quantile sets (or metronoids) and depth-trimmed regions. Its second part generalises [27,Th. 1.1], which concerns the case of ξ supported by a convex body.…”
Section: Average Quantile Sets As Integrated Depth-trimmed Regionsmentioning
confidence: 97%